Study of assessment of quality and maturity of fresh ginger - Noypitak, Sirinad; Terdwongworakul, Anupun; Kasemsumran, Sumaporn (Engineering and Applied Science Research, 2015)
The research studied evaluative method of physiological properties of three stages of fresh gingers including immature stage, early mature stage and mature stage to be alternative for quality checking of maturity fresh ginger. The classification models were built based on both destructive method and non-destructive methods. The destructive variables were texture parameters, crude fiber and moisture content and the non-destructive variables were specific gravity, color (L*, a*, b*), gloss and light reflection in range 400-700 nm. The results showed that increasing of ginger harvesting date significantly affected physiological properties. The partial least squares discriminant analysis (PLS-DA) was performed to create a classifying model for harvesting date of fresh ginger. The 55.56% and 100% best accuracy of classification into three stages of maturity could be achieved by the destructive model and the non-destructive model, respectively. The best applicable variables in building the non-destructive model were light reflection at 420, 450, 490, 530, 570, 590, 680 nm and the specific gravity